Novel allyl and propenyl monomers for modification of the bismaleimide resins, with excellent dielectric properties and high glass transition temperatures. (February 2020) - Qu, Chunyan; Chang, Jiaying; Liu, Changwei; Wang, Dezhi; Xiao, Wanbao; Su, Kai; Feng, Hao; Li, Liaoliao; Zhao, Daoxiang; Zheng, Shuai; Tang, Yao; Fan, Xupeng; et al.
Two new monomers were prepared by the reaction of 2-allylphenol and 4, 4′-biphenyldicarbonyl chloride under different reaction conditions. The monomers were characterized by Fourier transform infrared spectroscopy and nuclear magnetic resonance spectroscopy. The curing processes of N, N -4, 4′-bismaleimidodiphenylmethyene with 4, 4′-bis(2-allylphenyl) biphenyldicarbonylate (BABC) and 4, 4′-bis(2-propenylphenyl benzoate) ether (BPBE) were studied by rheological analysis and differential scanning calorimetry. Melting points of two monomers, BABC and BPBE, are 64°C and 121°C, respectively. The ABMI [4, 4′-bis(2-allylphenyl)biphenyl bismaleimide] and PBMI [4, 4′-bis(2-propenylphenyl)biphenyl bismaleimide] resins showed exothermic peaks at 233°C and 204°C, respectively. The measured melting points are significantly lower than that of the traditional bismaleimide resin which is modified by allyl bisphenol A. Dynamic mechanical analysis of the materials showed glass transition temperatures of ABMI and PBMI to be in the range of 213–258°C and 302–339°C, respectively. Thermogravimetric analysis of the cured resins showed 5% weight loss for ABMI and PMBI at 437°C and 428°C, along with char residues of 35.6–39.5%, respectively, at 800°C under nitrogen atmosphere. Furthermore, dielectric constants of propenyl-modified resins were lower (2.46–3.10) with dissipation factors of 0.0034–0.0036, compared with those of allyl bisphenol A resins.